CLINICAL AND HEMOGLOBIN PROFILE OF MALARIA PATIENTS IN KARITAS HOSPITAL, SOUTHWEST SUMBA, PERIOD OF YEAR 2017 - Johan, Alvin; Natalia, Audrey; Djauhari, William; Effendi, Rambu Farah (Indonesian Journal of Tropical and Infectious Disease, 2020)
Malaria infections in high endemic areas are not pathognomonic and often show non-specific symptoms. The Southwest Sumba district is a high endemic area of malaria with the annual parasite incidence (API) of 14.48"°. The research conducted in this area was to identify the clinical and hemoglobin profile of malaria patients and to obtain comprehensive information on the clinical characteristics of malaria in a high endemic area of Southwest Sumba district. This is a descriptive cross-sectional study. The data was obtained from the medical record of malaria patients between  January 1st and December 31st, 2017 in Karitas Hospital, Southwest Sumba district. Inclusion criteria were patients with asexual stages of Plasmodium spp. on their Giemsa-stained thick and thin peripheral blood smears examination. Exclusion criteria were malaria patients with coexisting diseases and who had taken medication before admitted to the hospital. The total number of patients was 322 patients, 50.6% of the subjects were â‰¥ 15 years old and 59.3% were male. Among 322  patients, 133 subjects were treated as inpatients. The result shows that most infection was caused by a single infection of P. falciparum.  The most common clinical symptom was fever (98.4%), followed by headache, vomiting, cough, and nausea. The most common physical finding was the axillary temperature of > 37.5°C (87.6%) followed by anemic conjunctiva and hepatomegaly, which was mostly found in pediatric patients. The number of patients with hemoglobin level â‰¤ 10 g/dL was 129. The MCV <80 fL was found in 79% of patients with anemia. Severe malaria was found in 116 subjects in this study according to severe malaria criteria set by the Indonesian Ministry of Health. Study results were consistent with other existing studies from other high endemic areas in East Nusa Tenggara province.